Evaluation of Acute and Subacute Oral Toxicity of Erlangea tomentosa (Oliv. & Hiern) S. Moore (Asteraceae) Methanol Leaf Extract in Experimental Wistar Albino Rats - Mboneye, Anselme; Onchweri, Albert Nyanchoka; Neeza, Timothy; Odoma, Saidi (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Erlangea tomentosa (Oliv. & Hiern) S. Moore's leaves, which are in the Asteraceae family, were tested for acute and subacute toxicity in experimental Wistar rats. Lorke’s (bi-phasic) method was used to evaluate the acute toxicity profile of the plant extract. In phase 2, twelve rats of both sexes were administered a maximum dosage of 5000 mg/kg of extract. Observations of toxicity signs were made and recorded for 2 hours consecutively, for 24 hours intermittently, as well as for the next 14 days. For the subacute study, rats were orally administered water and plant extract daily for 28 days. Toxicological effects were recorded daily, and body weights were documented weekly. Hematological, biochemical, and histopathological tests as well as relative organ weights were evaluated at the conclusion of the study. In phase 2 of the acute toxicity study, it was found that the plant extract was toxic at doses of 1600, 3100, and 5000 mg/kg, with only one death at the highest dose. In the subacute toxicity study, animals that were administered 800 mg/kg of extract for 28 days showed symptoms of toxicity. The weight of the kidneys increased; urea and ALT levels increased; as well as total protein and albumin levels decreased compared to the control group. At the same dose, histopathology examination revealed alterations of the liver and kidneys, while hematopoietic cells were significantly disrupted compared to the control animals. Based on the findings, the methanol-extracted leaves of E. tomentosa showed a moderate level of acute toxicity. The administration of the extract at a dose of 400 mg/kg was safe, but 800 mg/kg was toxic. This caused damage to their livers and kidneys. This led to an increase in ALT and ALP, changes in blood parameters like Hb, RBC, and PLT, as well as the development of inflammatory cells.